(untitled) - Moreno Serrano, José Antonio; Pérez Ruíz, César; Moreno Fierro, Ivonne; Moreno Fierro, Jorge (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Effect of culture medium on morphogenic processes in vitro in Cinchona officinalis L. (2019)

(untitled)
This paper describes the effect of the various plant growth regulators of the culture medium on morphogenic processes in vitro in Cinchona officinalis L, a highly vulnerable species from southern Ecuador. To do this, different concentrations of NaOCl were used in combination with different immersion times for seed disinfection; for seed germination in vitro GA3 was added to the MS basal culture medium in different concentrations, and for morphogenic processes in vitro, different concentrations of auxins and cytokinins were combined. The decrease in the contamination rate was with high concentrations of NaOCl and an increase in the germination rate in 45 days with the addition of 1.0 mg L-1 GA3 to the culture medium the hormonal combination of 0.5 mg L-1 NAA + 2.5 mg L-1 BAP showed a high rate of shoot proliferation and with 1.0 mg L-1 NAA a high number of roots was obtained. In the callogenesis phase, the best results were obtained with 1.0 mg L-1 2,4-D + 0.5 mg L-1 BAP for callus proliferation. In vitro propagation protocols were generated in Cinchona officinalis L, for the preservation and conservation of the species.